Assessing the market potential of electric bicycles and ICT for low carbon school travel: a case study in the smart city of Águeda - Arsénio, E. (2017)
Electric bikes (e-bikes) may help in transport decarbonisation in European cities. To fully assess the market potential of e-bikes, further research is needed to understand users’ preferences and the range of factors that can contribute for people to shift from car use to low carbon vehicles such as e-bikes. This paper is built on the Be4Schools R&D project implemented in the city of Águeda which is considered the first smart city in Portugal. It comprised the former study in the country that examined the willingness of students (aged 15-21 years) to use e-bikes for daily trips to school and that gathered their preferences towards specific ICT related attributes. The methodology comprised a mobility survey and a stated-choice experiment (SC). The SC experiment gathered 2232 observations which were able to provide the relevant attribute trade-off information between car travel and e-bike (with or without specific ICT equipment). An extensive econometric analysis was performed to assess the nature and extent of students’ heterogeneity of preferences which also considered gender issues. The study aimed to contribute to the regional economic cluster on powered two-wheels' industry & innovation. Research results are interesting for city mobility policies and the regional industry as the possible integration of ICT equipment in e-bikes may speed up the market uptake of this technology.